A Guide For Nurses And Respiratory Therapists In Cardiac Arrest Management - Reem Awad Al Anazi, Alya Thamer Alanazi, Alya Thamer Alanazi, Bashaier Hussien Ahmed Alshahrani, Murtada Shukri Bojubarah, Fadel Mohammed Alabdullah, Talal Eid Alanazi, Seusaen Ali Al Nasser; Afnan Faisal Jastaniyyah, Raed Hassan Alshehri, Rayan Mohammed Alanazi, Jumanah Abdulkarim Alqadhib, Ali Abdulaziz Albattat, Abdullah Ali Alramadan, Abdullah Ghaleb Albulihed (Journal of International Crisis and Risk Communication Research, 2024)
In-hospital cardiac arrest is a critical global health issue and a major cause of mortality in developed nations, with an estimated incidence of one to six events per 1,000 hospitalized patients. Immediate recognition and intervention, particularly through the initiation of cardiopulmonary resuscitation (CPR), are crucial for enhancing survival rates. Rapid response teams (RRTs) have been implemented as a key strategy to improve early detection and reduce mortality from in-hospital cardiac arrest. Nurses play a vital role in RRTs, providing critical care to acutely ill patients, upholding care quality, and training healthcare teams to identify clinical deterioration. However, the specific roles and contributions of nurses within these multidisciplinary teams remain underexplored. This review discusses the epidemiology, causes, management during and after cardiac arrest, factors influencing outcomes, prognostication, and strategies for quality improvement in adult in-hospital cardiac arrest. The global incidence and outcomes of in-hospital cardiac arrest vary across countries, with survival rates ranging from 13% to 30%. Cardiac etiologies account for approximately 50-60% of cases, while respiratory insufficiency is the second most frequent cause. Prevention of cardiac arrest through early identification of at-risk patients and rapid interventions is crucial. Treatment during cardiac arrest focuses on high-quality CPR, early defibrillation, and appropriate medication administration. Post-cardiac arrest management addresses the underlying cause, provides hemodynamic and respiratory support, and implements neuroprotective strategies. Numerous patient and event-related characteristics influence clinical outcomes, with age, preexisting conditions, presenting rhythm, and duration of cardiac arrest being strong predictors. Prognostication remains challenging, and a comprehensive, multifaceted approach is recommended. Quality improvement initiatives, such as participation in national registries and adherence to performance measures, can enhance outcomes following in-hospital cardiac arrest.